Procesy instytucjonalizacji socjologii w Polsce a recepcja socjologii światowej = Institutionalization processes of sociology in Poland and the perception of the world sociology - Kraśko, Nina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article is an attempt to answer the question of how research institutions influence the type of sociological research and teaching in sociology departments in Poland. Research institutions are indispensable for the development of social science. Even the most minimal cooperation between amateurs requires the creation of scientific institutions. The more any given discipline is institutionalized the more likely it is that the researchers working within the institution participate in national and not international investigations.
Keywords: socjologia; instytucjonalizacja; Polska